Sidekicks. [2], Thick as thieves - Santat, Dan (Santat, Dan. Sidekicks (Series) ;, 2026)
There's trouble at the Society of Superheroes! Captain Amazing, the longtime hero of Metro City, has retired, and he's enjoying a much-needed vacation at the World's Biggest Ball of Yarn. But while he's away, there's trouble at home! A massive data breech disrupts the Society of Superheroes, and a flash drive containing sensitive information about Captain Amazing and other heroes winds up in reckless hands. Meanwhile, an unannounced visitor named Whipley arrives at the captain's house, and his pet sidekicks -- Manny, Roscoe, and Fluffy -- are skeptical of the stranger's intentions. The only sidekick excited by the visit is Shifty. Could Whipley be Shifty's loving, long-lost brother as he claims? Or is he framing the sidekicks for his own personal gain and vengeance?